2019
DOI: 10.18632/aging.102270
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress-induced cellular senescence desensitizes cell growth and migration of vascular smooth muscle cells through down-regulation of platelet-derived growth factor receptor-beta

Abstract: The relationship between aging and restenosis are unclear. The purposes of this study were to investigate the possible pathological role and mechanism of aging on formation of restenosis. Our data indicated that cell proliferation and migration of the oxidative stress-induced senescent vascular smooth muscle cells were obviously desensitized to stimulation by platelet-derived growth factor (PDGF)-BB, which may have been caused by suppression of promoter activity, transcription, translation, and activation leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 60 publications
1
4
0
Order By: Relevance
“…Among them, FOXA1, PLAT, CD44, FGF5, DIO2 and other genes are upregulated, whereas PLCB1, SETBP1, EHD3, ZNF423, PHGDH and other genes are downregulated in multiple senescence systems(Chan et al, 2019; Cho et al, 2019; Galanos et al, 2016; Hari et al, 2019; Hernandez-Segura et al, 2017; Komseli et al, 2018; Lau, Porciuncula, Yu, Iwakura, & David, 2019; Leveque et al, 2019; Q. Li et al, 2013; Limbad et al, 2020; Lowe & Raj, 2014; Nagano et al, 2016; Pan et al, 2019; Pantazi et al, 2019; Suwan et al, 2009; Wu, Pepowski, Takahashi, & Kron, 2019; Zhou et al, 2010), as are consistent with our results. These genes are located in or near the regions of IARs or DARs respectively.…”
Section: Resultssupporting
confidence: 92%
“…Among them, FOXA1, PLAT, CD44, FGF5, DIO2 and other genes are upregulated, whereas PLCB1, SETBP1, EHD3, ZNF423, PHGDH and other genes are downregulated in multiple senescence systems(Chan et al, 2019; Cho et al, 2019; Galanos et al, 2016; Hari et al, 2019; Hernandez-Segura et al, 2017; Komseli et al, 2018; Lau, Porciuncula, Yu, Iwakura, & David, 2019; Leveque et al, 2019; Q. Li et al, 2013; Limbad et al, 2020; Lowe & Raj, 2014; Nagano et al, 2016; Pan et al, 2019; Pantazi et al, 2019; Suwan et al, 2009; Wu, Pepowski, Takahashi, & Kron, 2019; Zhou et al, 2010), as are consistent with our results. These genes are located in or near the regions of IARs or DARs respectively.…”
Section: Resultssupporting
confidence: 92%
“…In rodent studies, the aortic tissues from aged mice exhibit mitochondrial dysfunction, and both cellular and mitochondrial levels of ROS are elevated in aortic tissues and VSMCs from aged mice (237,243). VSMCs from aged mice display several characteristics, including a reduced proliferation and migration, an alteration in the response to contracting mediators, and a shift from "contractile" to "synthetic" phenotype (46,178). Senescence aortic SMCs also exhibit mitochondrial DNA damage, increased ROS generation, increased lipid peroxidation, and decreased GSH and GSSG concentrations (165).…”
Section: Other Factors Associated With Vascular Diseasementioning
confidence: 99%
“…Our results showed that both single (Cd, Co, Cs, Pb, and Tl) and mixed metals were positively associated with biological aging. Consistent toxicological evidence presented that heavy metals can induce senescence in stromal and vascular smooth muscle cells (e.g., Co and Cd) [35,36], as well as accelerate brain aging in animals, shown by damaged molecules and impaired energy metabolism [17]. Also, a recent population study indicated the positive associations between heavy metals (e.g., Co) and biological aging marker (DNA methylation age) [37].…”
Section: Discussionmentioning
confidence: 83%